Guillain–Barré syndrome initially manifesting as motor weakness, urinary dysfunction and hyperreflexia: Case report and literature review. Issue 2 (28th October 2017) - Oji, Satoru; Narukawa, Shinya; Ishizuka, Keita; Sugimoto, Kohei; Yoshida, Norihito; Takeshita, Hideki; Kaida, Ken‐ichi; Nomura, Kyoichi
Abstract: Background: Guillain–Barré syndrome (GBS) is an acute inflammatory neuropathy characterized by areflexic quadriparesis. Urinary dysfunction has been known to occur in approximately 25% of GBS patients during the clinical course and usually emerges during peak motor weakness. According to the diagnostic criteria for GBS, bladder dysfunction at onset makes the diagnosis of GBS rather doubtful. We report here a rare case of GBS that initially manifested as motor weakness with urinary dysfunction and hyperreflexia. Case presentation: A 66‐year‐old Japanese man experienced mild weakness in his hands that extended to the entire upper extremities the following day. At the same time, he started experiencing difficulty voiding. On the fourth day after the onset of weakness, he was admitted to Saitama Medical Center, Kawagoe, Japan, because of an inability to stand up without support. Neurological examination revealed moderate generalized weakness, hyperreflexia, and poor urinary volume and flow. Early in hospitalization, his deep tendon reflexes gradually decreased and ultimately he became areflexic. A nerve conduction study indicated the axonal form of GBS. He was treated with immunoadsorption plasmapheresis, followed by two sessions of intravenous immunoglobulin G treatment. The motor weakness and urinary dysfunction gradually ameliorated, and he was discharged and transferred for rehabilitation on hospital day 47. Conclusions: The present case suggests that urinary dysfunction in GBS might not necessarily occur during peak motor weakness, but could start at onset. Physicians should consider GBS in differential diagnosis of patients presenting with initial symptoms of motor weakness and urinary dysfunction. Abstract : A urodynamic study showed detrusor overactivity during the storage phase, weak detrusor contractility during the voiding phase and mild obstruction.